Managing the informal economy: a theoretical debate in the light of gig economy - Vaclavik, Marcia Cristiane (2022)
Informality is a historical feature of the Brazilian labor market. Its economic and social importance is undeniable. In this essay, considering the gig economy and digital labor markets phenomenon, we argue that a process of “managing the informal economy” is underway. It is observed that big companies are mediating labor relations through online platforms, using informal work. This phenomenon reorganizes and amplifies informality, creating a new employment statute by merging characteristics of formality (such as control, performance evaluation, and financial incentives) and informality (due to the autonomous nature and the lack of employment relationship with the organization). In Brazil, app-based work has grown substantially, reinforcing the need for theoretical and empirical investigation.